Mortality and cancer incidence among Swedish paint industry workers with long-term exposure to organic solvents. - Lundberg, Ingvar (Scandinavian Journal of Work, Environment & Health, 1986)
Cause-specific mortality was studied in a cohort of 416 men who had worked for at least five years in the Swedish paint manufacturing industry during the period 1955-1975. The calculations of expected numbers were based on national, male, calendar-year, and cause-specific death rates for the period 1961-1981. Ninety-six paint industry workers had died, whereas 110 deaths were expected. Three workers had died from multiple myeloma (0.6 expected), and the excess might be related to solvent exposure. Three cleaners had died from infectious urinary tract disease, in comparison to 0.2 deaths expected from all genitourinary diseases, in this small and very heavily exposed group. This association might possibly indicate a modifying effect on the prognosis of urinary tract morbidity from solvents.